2019
DOI: 10.1101/733105
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early post-zygotic mutations contribute to congenital heart disease

Abstract: 53Background 54The contribution of somatic mosaicism, or genetic mutations arising after oocyte fertilization, to congenital 55 heart disease (CHD) is not well understood. Further, the relationship between mosaicism in blood and 56 cardiovascular tissue has not been determined. 58Results 59We developed a computational method, Expectation-Maximization-based detection of Mosaicism (EM-60 mosaic), to analyze mosaicism in exome sequences of 2530 CHD proband-parent trios. EM-mosaic 61 detected 326 mosaic mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
(85 reference statements)
1
2
0
Order By: Relevance
“…Our cohort, with three proband-derived tissue samples, allows us to explicitly test this alternative hypothesis. We found that an average of 1.5% of the de novo variants in the proband's blood were not germline in origin (not present in all three proband tissues) and is a similar rate as found in other recent papers [58,99]. In fact, in proband 411 a blood-specific somatic variant in MIR4717 would have been classified as a germline variant.…”
Section: Discussionsupporting
confidence: 86%
“…Our cohort, with three proband-derived tissue samples, allows us to explicitly test this alternative hypothesis. We found that an average of 1.5% of the de novo variants in the proband's blood were not germline in origin (not present in all three proband tissues) and is a similar rate as found in other recent papers [58,99]. In fact, in proband 411 a blood-specific somatic variant in MIR4717 would have been classified as a germline variant.…”
Section: Discussionsupporting
confidence: 86%
“…We found that an average of 1.5% of the de novo variants in the probands’ blood were not germline in origin (not present in all three proband tissues) and is a similar rate as found in other recent papers. 93 , 123 In fact, in proband 411, a blood-specific somatic variant in MIR4717 would have been classified as a germline variant. Thus, researchers should be cautious about inferring that all de novo variants in the blood are germline in origin.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we developed a computational method, EM-mosaic (Expectation-Maximization-based detection of Mosaicism) [35], to detect mosaic single-nucleotide variants (SNVs) using WES of proband and parent DNA. To optimize this method, we measured mosaic detection power as a function of sequencing depth.…”
Section: Introductionmentioning
confidence: 99%